The debated role of bariatric surgery in improving in-vitro fertilization outcomes in morbidly-obese infertile women-a case report and brief overview - Yi-En Chang; Tzu-Ning Yu; Ching-Hui Chen; Szu-Yuan Chou; Buo-Jia Lu; Chi-Huang Chen (Elsevier, 2021)
Objective: Obesity has a negative impact on in-vitro fertilization (IVF) outcomes, and obese women who plan IVF treatments are often encouraged to pursue weight reduction. Bariatric surgery is an effective strategy for the treatment of morbidly obese women. The current case report is to investigate the impact of bariatric surgery on IVF outcome in a morbidly obese woman with subfertility. Case report: A 37-year-old, morbidly obese woman with subfertility was indicated for IVF treatment. Due to her high body mass index (47.9 kg/m2), she was advised to lose weight; initial failure at conservative measures of weight loss prompted her to undergo bariatric surgery, combined with post-operative lifestyle change, prior to receiving IVF treatment. The woman successfully conceived at the second cycle and delivered twins by cesarean section smoothly at 36 + 3/7 weeks of gestation. Both twins have normal development up to two years of age. Conclusions: Weight reduction mediated by bariatric surgery in subfertile and morbidly obese women can be considered before IVF treatment.